2008
DOI: 10.1248/bpb.31.1362
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Effects of Bofutsushosan on Obesity and Various Metabolic Disorders

Abstract: Visceral fat accumulation induces insulin resistance, abnormal glucose metabolism, abnormal lipid metabolism and hypertension. Furthermore, even when these individual diseases are present in only a mild form, if more than one of these diseases is present, this may induce development of arteriosclerosis or ischemic cardiovascular diseases.1,2) For these reasons, it is important that some form of medical therapy including exercise and diet therapy be devised to prevent the development of obesity and various meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 19 publications
(18 reference statements)
3
42
2
Order By: Relevance
“…Thus far, it has been reported that blood TG levels in TSOD mice are greater than those in TSNO mice. 29,33 These data suggest that the hepatic dysfunction observed early in time is associated with the development of fatty liver disease in TSOD mice. In the visceral fat, enlargement of adipocytes, perivascular and pericapsular CD8-positive lymphoid aggregations, and CLSs with macrophage aggregation were observed after 4 months of age.…”
Section: Discussionmentioning
confidence: 76%
“…Thus far, it has been reported that blood TG levels in TSOD mice are greater than those in TSNO mice. 29,33 These data suggest that the hepatic dysfunction observed early in time is associated with the development of fatty liver disease in TSOD mice. In the visceral fat, enlargement of adipocytes, perivascular and pericapsular CD8-positive lymphoid aggregations, and CLSs with macrophage aggregation were observed after 4 months of age.…”
Section: Discussionmentioning
confidence: 76%
“…CT-based analysis of body composition was performed after 12 wk of Aloe vera gel treatment (at 23 wk of age). The rats were anesthetized with isoflurane (Dainippon Sumitomo Pharma, Osaka, Japan) and scanned from xiphisternum to sacrum at 2 mm intervals using LaTheta (LCT-100A), an experimental X-ray CT instrument (Aloka Co., Ltd., Tokyo) ( 19 ). The estimated amounts of visceral and subcutaneous fat tissues, and percentage of body fat were calculated using LaTheta software.…”
Section: Methodsmentioning
confidence: 99%
“…23,24) Geniposide showed preventative effects on various metabolic disease symptoms in the TSOD mice. The body weight increase seen in the TSOD mice was significantly suppressed by geniposide from the 5th week after starting the treatment.…”
Section: Discussionmentioning
confidence: 95%